2015
DOI: 10.1111/are.12831
|View full text |Cite
|
Sign up to set email alerts
|

Eastern little tuna,Euthynnus affinis(Cantor, 1849) mature and reproduce within 1 year of rearing in land-based tanks

Abstract: Eastern little tuna (ELT, Euthynnus affinis) is expected to see use as a novel aquaculture species due to its rapid growth and high economic value. In this study, closing of the complete life cycle of ELT in land‐based tanks was successfully carried out. Seed production of a first generation (F1) derived from wild‐caught ELT broodstock was conducted in 2010, 2011 and 2012. Survival percentages of F1 ELT at 365 days post hatching for the 2010, 2011 and 2012 year classes were 0.9%, 0.4% and 6.3% respectively. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Although we did not investigate the growth rates of seedlings produced in this study, ELT seedlings produced in May 2013 in our rearing system reached a BW of nearly 2 kg and TL of 40 cm at 200 days after hatching in December 2013 when the temperature of natural seawater dropped below 20°C (Yazawa et al . ). Since juveniles that reach a TL of approximately 30 cm by the beginning of the low‐temperature season typically show high survival through the winter period (Takeuchi et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although we did not investigate the growth rates of seedlings produced in this study, ELT seedlings produced in May 2013 in our rearing system reached a BW of nearly 2 kg and TL of 40 cm at 200 days after hatching in December 2013 when the temperature of natural seawater dropped below 20°C (Yazawa et al . ). Since juveniles that reach a TL of approximately 30 cm by the beginning of the low‐temperature season typically show high survival through the winter period (Takeuchi et al .…”
Section: Discussionmentioning
confidence: 97%
“…). We also successfully demonstrated completion of the ELT life cycle in 38‐m 3 land‐based tanks (Yazawa, Takeuchi, Amezawa, Sato, Iwata, Kabeya & Yoshizaki ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, we also showed that the death rate of triploids was significantly higher than that of the diploids during the 2–4 weeks post‐hatching period when both the triploids and diploids were reared in the same tank. During this developmental stage, ELT juveniles showed high mortality due to their piscivorous behavior and cannibalism (Yazawa et al, ). Since triploid ELT could survive when reared individually (data not shown), it is speculated that triploid fish were selectively attacked by diploid fish.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ELT has attracted considerable attention as an alternative for the conventional aquaculture species in Japan due to its high commercial value and high growth performance. In previous studies, we developed the technique for the induction of natural spawning by the administration of gonadotrophin‐releasing hormone agonist (GnRHa) to ELT broodstock (Yazawa et al, ) and also successfully demonstrated completion of the ELT life cycle in a land‐based tank (Yazawa et al, ). Moreover, we have established a method for the stable and year‐round production of ELT seed by GnRHa administration (Yazawa et al, ).…”
Section: Introductionmentioning
confidence: 99%